Pengaruh Human Relation, Kepemimpinan dan Lingkungan Kerja Fisik Terhadap Etos Kerja pada Pegawai DIKPORA Kota Taliwang Kabupaten Sumbawa Barat - Suhartini, Yati; Setiawan, Rivan; Imam Basri, Anindita (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2023)
This study aims to determine the effect of Human Relations, leadership, and the work environment on the work ethic of employees DIKPORA, West Sumbawa. The research was conducted from June to August 2023. This research was analysized using multiple linear regression with the help of the SPSS 25.0 program. Total population are 65 employees. Data collection have done by questionnaires. The results of the study were Human Relations had a positive effect on work ethic with a sig value of 0.022 <0.05, leadership had a positive effect on work ethic with a sig value of 0.004 <0.05, the work environment had a positive effect on work ethic with a sig value of 0.041 <0.05. Human relations, leadership, and the work environment simultaneously had a significant effect on work ethic as evidenced by the F count value of 37,292 > Ftable 2.75 and a significance value of 0.000 <0.05. The results of the F test are supported by adjusted R square value of 0.630.